Hotel chains in Ukraine: structural and spatial organization and the trends in the hotel business corporatization (Economics and region, 2023)
The article improves the theory and methodology of the corporatization of the hotel services market of Ukraine by national and international operators. The main types of operators of the Ukrainian hotel market are highlighted. The peculiarities of the organization of international and national hotel corporations, economic and spatial expansion in the national market of hotel services are analyzed. The influence of factors of investment attractiveness, the cost of housing purchasing and rent, the average salary, the passenger flow volume in the airports, etc. on the presence of hotel chains has been determined. The main factor attracting hotel operators to Ukraine is identified – unsatisfied demand for hotel services, in particular of the international quality level. Clear differentiation and division of Ukrainian corporations into general national and local ones has been traced. National chains are characterized by geographical presence in all the regions of Ukraine. The market of corporate forms of hotel business in Ukraine is at the stage of formation, it is characterized by the involvement of foreign hotel corporations and the development of national hotel brands. The gravitation of international hotel corporations to the main centers of business activity and tourist destinations of Ukraine has been revealed.
Keywords: hotel chains; corporatization of the market of hotel services; international and national hotel operators; spatial expansion; Ukraine